FENOMENA PEKERJA ANAK DITINJAU DARI PERSPEKTIF HAK ASASI MANUSIA - Suharyanti, Ni Putu Noni; Setiawan, Kadek Endra (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2017)
The child labour are vulnerable to exploitation and violence that affect the physical, mental, moral, and spiritual development of the child so that should be protected. The Government has demonstrated its commitment through ratification of the international conventions on child labour namely the ILO Convention Number 138 of 1973 and ILO Convention Number 182 of 1999. In addition, Law of the Republic Indonesia Number 13 Year 2003 concerning Employment has also provided protection for child labour. The existence of child labour is difficult to elliminate because the economic factors are often the main reason why children should work so that full prohibition of children to work in this condition triggered a dilemma for the government. Protecting child labour is not enough by establishing a legal product but must be accompanied by supervision and enforcement of sanctions against actors who employ children not in accordance with applicable regulations. Therefore, to protect child labour from exploitation, violence, or anything else that triggers the loss of child rights requires a comprehensive effort by various parties.